Influence of Principals’ Leadership Styles and Resource Management Practices on Performance among Public Secondary Schools in Plateau State, Nigeria - ONU; Eucharia Amaka; IDRISJEREMIAH Idris (Federal University Gusau Faculty of Education Journal, 2026)
This study aimed to evaluate principal’s leadership styles and resource management with focus on the implication for Public secondary schools performance within Plateau state. Three research question and three hypotheses guided the study the study adopted a descriptive survey research design, the population of this study shall be 304 public secondary schools, 4310 individuals comprising of 598 principals who consist of 304 junior secondary school principals and 294 senior secondary school principals and 3712 teachers. A sample size of 201 which comprises of 81 principals for both junior and senior section and 120 teachers was drawn using simple random sampling techniques from 58 public secondary schools from the three (3) sampled Local Government Areas (One from each senatorial zone) of Plateau State. The instruments for data collection for this study were structured questionnaire. The questionnaire was titled (Principals’ Leadership Styles and Resource Management Practices and Implications for Secondary School Performance Questionnaire) (PLSRMPISSPQ). The instruments were validated and the reliability coefficient of greater than 0.70 determined. The findings revealed among others that Schools led by principals who involved teachers in decision-making, encouraged teamwork, motivated staff, and provided clear direction recorded higher levels of students' academic achievement, improved teacher job performance, and better student discipline. The principals who efficiently managed human, financial, material and time resources achieved better educational outcomes. Proper allocation of funds, adequate supervision of teachers, maintenance of school facilities, and effective time management contributed positively to students' academic performance, teachers' productivity, and the overall effectiveness of public secondary schools.